2010
DOI: 10.1037/a0021140
|View full text |Cite
|
Sign up to set email alerts
|

For God (or) country: The hydraulic relation between government instability and belief in religious sources of control.

Abstract: It has been recently proposed that people can flexibly rely on sources of control that are both internal and external to the self to satisfy the need to believe that their world is under control (i.e., that events do not unfold randomly or haphazardly). Consistent with this, past research demonstrates that, when personal control is threatened, people defend external systems of control, such as God and government. This theoretical perspective also suggests that belief in God and support for governmental systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(189 citation statements)
references
References 70 publications
5
177
2
5
Order By: Relevance
“…That is, men appear to be defending traditional relationship ideology not only because of its relation to the larger socio-political system that people are motivated to defend (Jost & Banaji, 1994), but also because of its utility in preserving male dominance (Sidanius & Pratto, 1999). Whereas the hydraulic relation between support for political and relational systems observed in Studies 1-4 is unique to system justification theory (e.g., Jost, Ledgerwood, & Hardin, 2008;Kay, Shepherd, et al, 2010;Wakslak, Jost, & Bauer, in press), the fact that this effect is strongest for men, especially when their dominance is most under threat, fits well with a social dominance approach (Sidanius & Pratto, 1999).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…That is, men appear to be defending traditional relationship ideology not only because of its relation to the larger socio-political system that people are motivated to defend (Jost & Banaji, 1994), but also because of its utility in preserving male dominance (Sidanius & Pratto, 1999). Whereas the hydraulic relation between support for political and relational systems observed in Studies 1-4 is unique to system justification theory (e.g., Jost, Ledgerwood, & Hardin, 2008;Kay, Shepherd, et al, 2010;Wakslak, Jost, & Bauer, in press), the fact that this effect is strongest for men, especially when their dominance is most under threat, fits well with a social dominance approach (Sidanius & Pratto, 1999).…”
Section: Resultsmentioning
confidence: 96%
“…Past work on system justification has demonstrated that systems are defended, in part, because they provide a sense of predictability and order in a sometimes unpredictable world, that is, they can serve as an external source of control (Jost & Hunyady, 2005;Kay & Jost, 2003;Kay, Shepherd, et al, 2010; see also Lerner, 1980). Thus, a more specific way to examine whether the system justification motive influences the defense of committed relationship values would be to assess whether perception of relationships as a means of external control contributes to the defense of this ideology.…”
Section: Study 4: Relationships As a Perceived Source Of Structure Omentioning
confidence: 99%
“…People who lack personal control perceive increased structure in random arrays (i.e., see pictures in static; Whitson & Galinsky, 2008) and believe more strongly in agents that impose structure on the world, such as a controlling god or a controlling government (Kay, Gaucher, Napier, Callan, & Laurin, 2008;Kay, Moscovitch, & Laurin, 2010;Kay, Shepherd, Blatz, Chua, & Galinsky, 2010;Shepherd, Kay, Landau, & Keefer, 2011). People lacking personal control also endorse scientific theories that suggest orderliness rather than randomness (Rutjens, van Harreveld, & van der Plight, 2010;Rutjens, van Harreveld, van der Plight, Kreemers, & Noordeweir, 2013;Rutjens, van der Plight, & van Harreveld, 2010), and folk beliefs that provide orderly explanations for negative events (e.g., that they are "a blessing in disguise") can foster a more global sense of control (Chipperfield et al, 2012).…”
Section: Compensatory Controlmentioning
confidence: 99%
“…Gray & Wegner, 2010). Moreover, empirical investigations of Kay et al's (2008) model of compensatory control have demonstrated that people in cultures across the globe tend to view God as a crucial contributing factor to the events that unfold in their lives, especially when the need for explanation is heightened Kay, Shepherd, Blatz, Chua, & Galinsky, 2010;Laurin et al, 2008). Research has also shown that because Christians believe in God, they are more likely to attribute improbable events to fate and to endorse the principle of equifinality-that is, to believe that events that take place would have occurred no matter what had preceded them (Norenzayan & Lee, 2010).…”
Section: God and Active Goal Pursuitmentioning
confidence: 99%